Dielectric spectroscopy and thermally stimulated discharge current in PEEK film - Sakamoto, Walter Katsumi (Eclética Química, 2003)
The complex permittivity of films of polyether ether ketone (PEEK) has been investigated over a wide range of frequency. There is no relaxation peak in the range of 1Hz to 10 5 Hz but in the low- frequency side (10 -4 Hz) there is an evidence of a peak that also can be observed by thermally stimulated discharge current measurements. That peak is related with the glass transition temperature (T g ) of the polymer. The activation energy of the relaxation was found to be 0.44 eV, similar to that of several synthetic polymers. Space charges are important in the conduction mechanism as shown by discharging transient.